2018
DOI: 10.1016/j.jmii.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Testicular infection in brucellosis: Report of 34 cases

Abstract: In endemic regions brucellosis should be taken into consideration in any patient with testicular infection. Brucellar testicular involvement is usually characterized with a severe acute clinical presentation and a high percentage of relapses which entails the need of timely recognition and proper treatment duration of at least 60 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Clinically it can manifest differently and can affect any organ system. The most common, genitourinary presentation is brucellosis epididymo-orchitis (BEO), which in endemic areas have been reported to account for 1.6%–12.7% of brucellosis 3. These can occur at any stage of the disease, either as the initial presentation or as a late complication.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically it can manifest differently and can affect any organ system. The most common, genitourinary presentation is brucellosis epididymo-orchitis (BEO), which in endemic areas have been reported to account for 1.6%–12.7% of brucellosis 3. These can occur at any stage of the disease, either as the initial presentation or as a late complication.…”
Section: Introductionmentioning
confidence: 99%
“…In these data, although 19 patients had a clear history of contact with cattle and sheep, this information is often neglected in the process of epidemiological data collection, which may lead to misdiagnosis and missed diagnosis. A published study 3 showed that even in endemic areas, it is difficult for doctors to diagnose brucellosis when the patient only shows orchitis. Through this study, we found that most of the patients came from farming and pastoral areas.…”
Section: Discussionmentioning
confidence: 99%
“…BEO'lu olguların yaklaşık %10'unda ise bilateral tutulum gözlenmektedir. [8] Literatürle uyumlu olarak yaş ortalaması 33 yıl olan BEO'lu olgularımızın tamamında unilateral testis tutulumu gözledik. Skrotal ağrı ve şişlik BEO'lu olgularda en sık görülen semptomlardır.…”
Section: Discussionunclassified